CpG island hypermethylation in human astrocytomas - Wu, Xiwei (2010)
Astrocytomas are common and lethal human brain tumors. We have analyzed the methylation status of over 28,000 CpG islands and 18,000 promoters in normal human brain and in astrocytomas of various grades using the methylated-CpG island recovery assay (MIRA). We identified six to seven thousand methylated CpG islands in normal human brain. ~5% of the promoter-associated CpG islands in normal brain are methylated. Promoter CpG island methylation is inversely and intragenic methylation is directly correlated with gene expression levels in brain tissue. In astrocytomas, several hundred CpG islands undergo specific hypermethylation relative to normal brain with 428 methylation peaks common to more than 25% of the tumors. Genes involved in brain development and neuronal differentiation, such as BMP4, POU4F3, GDNF, OTX2, NEFM, CNTN4, OTP, SIM1, FYN, EN1, CHAT, GSX2, NKX6-1, PAX6, RAX, and DLX2, were strongly enriched among genes frequently methylated in tumors. There was an overrepresentation of homeobox genes and 31% of the most commonly methylated genes represent targets of the Polycomb complex. We identified several chromosomal loci in which many (sometimes more than 20) consecutive CpG islands were hypermethylated in tumors. Seven of such loci were near homeobox genes, including the HOXC and HOXD clusters, and the BARHL2, DLX1, and PITX2 genes. Two other clusters of hypermethylated islands were at sequences of recent gene duplication events. Our analysis offers mechanistic insights into brain neoplasia suggesting that methylation of genes involved in neuronal differentiation, in cooperation with other oncogenic events, may shift the balance from regulated differentiation towards gliomagenesis.